VARIABEL PERTUMBUHAN EKONOMI, BELANJA DAERAH, INVESTASI, KURS, DAN KRISIS EKONOMI DALAM PEREKONOMIAN JAKARTA 1987-2017 - Yurianto Yurianto (UNIVERSITAS INDRAPRASTA PGRI, 2020)
The economy of Jakarta is the largest contributor to the national economy, and greatly affects the national economy. The research objective is to identify the variables of economic growth, regional spending, investment, exchange rates and to identify the effects of regional spending variables, investment, exchange rates, and the economic crisis on economic growth. This study uses descriptive-quantitative analysis and multiple linear regression methods. The economic growth of Jakarta in the 1987-2017 period tends to increase. The 1998 economic crisis has corrected economic growth. The ratio of direct expenditure to total expenditure and investment has a positive and significant effect on economic growth. Exchange rate depreciation has a negative relationship with economic growth. The economic crisis has a negative effect on economic growth. It was recommended to the TAPD (Regional Government Budget Team) Jakarta to allocate more direct expenditure than indirect expenditure